Konsep Pembangunan Pariwisata Milenial Di Kabupaten Buleleng - I Gede Sutana; Ida Bagus Gede Paramita (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The purpose of the research is to provide an alternative pattern of tourism development with the main market share of the millennial generation. This is very suitable considering the potential of nature, tradition and culture in Buleleng regency to support millennial tourism development. The driving factors such as image, characteristics and motives in traveling also support the development of this tourism. In addition, steps that can be taken for tourism development are also offered, namely, by holding tourism events, digital tourism, and sustainable tourism. This research is descriptive-qualitative research. Primary data in this study is sourced from observations and interviews while secondary data from scientific journals and books that help this research. The collected data is then selected to assist the analysis and the last step is drawing conclusions. The results of this study are a recommendation for the local government of Buleleng regency to develop tourism with a millennial market share.Keywords: Tourism Development, Millennial Tourism.